1996
DOI: 10.1143/jjap.35.1593
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Formation on Si(100)-2×1 Surfaces Studied by Scanning Tunneling Microscopy/Scanning Tunneling Spectroscopy

Abstract: A comparison is made between 'Born' and 'binary-encounter' generalized oscillator strengths of the continuum states of hydrogen for hydrogen atom impact. The results of this comparison show that resonance excitations are less important for ionization by hydrogen atom impact than for ionization by proton impact and that, consequently, the Born and binary-encounter approximations will be in closer agreement in the former case than in the latter case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 2 publications
5
25
0
Order By: Relevance
“…The oxidation of Si(1 0 0) leads furthermore to the appearance of bright protrusions, observed as such at both positive and negative bias [26,27]. The apparent height of the bright protrusions has been reported to be 1.4 Å [27], in good agreement with the 1.5 Å found in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The oxidation of Si(1 0 0) leads furthermore to the appearance of bright protrusions, observed as such at both positive and negative bias [26,27]. The apparent height of the bright protrusions has been reported to be 1.4 Å [27], in good agreement with the 1.5 Å found in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…The most straightforward explanation is therefore that the dark patches (labelled E in Fig. 1b) SiO x gives rise to dark patches following the high symmetry directions [25][26][27]. These patches appear as depressions at both positive and negative bias.…”
Section: Discussionmentioning
confidence: 99%
“…STM studies of ultrathin silica films on Si wafers reported very similar bias conditions to image the silica oxide layer. 20,21 In addition, it has been found in this study that a sample bias higher than ϩ6 V…”
mentioning
confidence: 48%
“…To obtain ⌬ for bulk Si(100)2ϫ1, we first measured the square conductance G 2ϫ1 (T) of the n-type bulk Si(100)2ϫ1 sample in UHV from TϷ120 K to 300 K. Next, we saturated the clean Si(100)2ϫ1 surface with O 2 at RT. This procedure destroys the reconstruction ͑as evidenced by a 1ϫ1 LEED pattern͒, eliminates the surface states, 21 and creates a flat-band surface according to band bending measurements with Si 2p core level spectroscopy. 22 The conductance of the oxidized sample G O 2 was then measured from 120 K to 300 K and we obtained ⌬(T)ϭG 2ϫ1 (T) ϪG O 2 (T).…”
Section: Methodsmentioning
confidence: 99%